Aspirin and Clopidogrel Resistance in Coronary Artery Disease - Fera Hidayati; Bambang Irawan; Hasanah Mumpuni (ACI (Acta Cardiologia Indonesiana), 2017)
Dual antiplatelet therapy has been proven effective to reduce recurrent cardiovascular eventin patients with coronary artery disease and recommended as standard therapy for acute coronary syndrome and patients who underwent percutaneous coronary intervention. The adverse clinical occurrence in patients who taking aspirin and clopidogrel associates with antiplatelet non responsiveness, in addition to repetitive bleeding incident in such a way that platelet reactivity and genetic polymorphisms investigation rises intense interest. Resistance to antiplatelet or antiplatelet non responsiveness means a phenomenon in which antiplatelet drug fails to deliver pharmacological target and it is determined by platelet function measurement. Recent laboratorymethods have been developed to diagnose antiplatelet resistance, but none of them was considered as standard tool since its wide inter-individual variability and poor correlation between them. The mechanism of antiplatelet resistance is not fully understood, multifactorial, involving pharmaco dynamic and pharmacokinetic of the drugs. This review is aimed to comprehend theantiplatelet resistance mechanism and provide crucial information on managing patients who take dual antiplatelet treatment with adverse clinical events.